Research on vertical GaN devices based on gradient Al components - Chen, Yonghe; Yang, Ye; Zhai, Jianghui; Sun, Yuanyuan (Frontiers in Physics, 2023)
A groove-gate power device with a linearly gradient Al composition P-type AlGaN superjunction (abbreviated as LG-SJCAVET) is proposed, which uses polarized P-type AlGaN material instead of the traditional P-type GaN buried layer, avoiding the technical bottleneck of achieving high-aspectratio P-type doping in GaN materials. Simulation results show that, under the same structural parameters, the breakdown voltage of LG-SJCAVET reaches 2954V, and the on-resistance is 1.669 2 m cm  , which is due to no current flowing through the P-pillar, resulting in an increase in onresistance, while affecting the DC characteristics of the device. The power figure of merit of the device is 5.27 2 / GW cm , which is 67.11% and 27.38% higher than that of the traditional device and P-type GaN buried layer device, respectively. Therefore, the LG-SJCAVET device solves the problems of the high technical difficulty of the traditional P-type GaN buried layer process, difficulty in activating acceptor impurities, and poor thermal stability of the device, exhibiting superior breakdown voltage characteristics.